Legal Transplant and the Model of Constitutional Court Decision - Bisariyadi Bisariyadi (Faculty of Law, Universitas Padjadjaran, 2018)
AbstractThe Indonesian Constitutional Court may, at times, uses concepts and models of laws from other countries. The transplantation of foreign laws can be organic or mechanic. The model of legal transplantation in the procedural law is an organic transplantation. The transplants can be problematic since it requires a compliance with the legal system in the recipient system. This article focuses on the practices of legal transplant by the Indonesian Constitutional Court in its procedural laws, especially in regards to their decisions. It mainly concerns on (i) the formulation of constitutional injuries criteria to give standing for parties to access before the Court; and (ii) the adoption of conditional (un)constitutionality decisions. It also discuss the source from which the Court find the similar practices and to what extend the Court made some adjustments in order to suits in its procedural law. The article also argue that legal transplant in procedural law may found adversities. In order to overcome these, the Court needs to made alteration to the foreign laws.AbstrakMahkamah Konstitusi kerap mencangkok konsep dan model hukum yang berlaku di berbagai negara untuk diadopsi dalam putusan Mahkamah Konstitusi, baik dalam arti pencangkokan yang bersifat organis maupun mekanis. Pencangkokan hukum dalam hukum acara termasuk dalam sifatnya yang organis. Model transplantasi ini bisa memicu pada ketidaksesuaian dalam penerapannya pada hukum acara pada sistem hukum yang akan mengadopsinya. Tulisan ini menitikberatkan pada praktik Mahkamah Konstitusi yang mencangkok model hukum asing untuk diterapkan dalam hukum acara terutama dalam perumusan model putusannya. Yang menjadi perhatian dalam tulisan ini adalah mengenai (i) penentuan kriteria kerugian konstitusional dalam kedudukan hukum pemohon (legal standing); dan (ii) jenis putusan (in)konstitusional bersyarat (conditionally (un)constitutional). Tulisan ini akan menyigi sumber inspirasi Mahkamah Konstitusi menemukan model tersebut serta sejauh mana pengembangan yang dilakukan oleh Mahkamah Konstitusi. Tulisan ini bertujuan untuk membuktikan bahwa pencangkokan model hukum asing dalam hukum acara Mahkamah Konstitusi juga menemukan beberapa hambatan. Dalam rangka menghadapi hambatan tersebut, Mahkamah Konstitusi melakukan penyesuaian atas konsep hukum asing yang diadopsinya. DOI: https://doi.org/10.22304/pjih.v5n1.a1